PEMIKIRAN SUFISTIK MUHAMMAD SHALIH AL-SAMARANI - Muhammad In’amuzzahidin (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2012)
The ideas of sufism of Muhammad Shalih al-Samarani in Matn al-Ḥikam and Majmū‘at al-Sharī‘ah al-Kāfiyah li ’l-‘Awām is still rarely studied by researcher. The sufism of Muhammad Shalih al-Samarani emphasizes on implementing islamic doctrine with sincerity and submition to God. Muhammad Shalih bases his sufism on practical (sunni-amali) sufism. He reject philosophical (falsafi) sufism, embraced by especially lay people.***Ide tentang sufismeMuhammad Shalih al-Samarani dalam Matn al-Ḥikam dan Majmū‘at al-Sharī‘ah al-Kāfiyah li ’l-‘Awām masih jarang dikaji. Sufisme Muhammad Shalih alSamarani menekankan implementasi doktrin Islam dengan ketundukan kepada Tuhan. Muhammad Shalih mendasarkan sufismenya pada sufisme praktis (sunni-amali). Dia menolak sifisme filosofis (falsafi), yang khususnya dianut oleh masyarakat awam.